The TGF-β3 Gene Polymorphisms and Carcass Components in Kampung x Meat Type Chicken Cross - I. Khaerunnisa; Jakaria; C. Sumantri (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2020)
The TGF-β3 gene is a subtype of TGF-β superfamily that plays a crucial role in skeletal muscle growth. The objectives of this study were to identify the TGF-β3|BslI locus polymorphisms and to evaluate their effects on carcass components in Kampung and broiler chicken cross. A total of 129 chickens used in this study, consisting of: Kampung chickens (44), parent stock broilers Cobb strains (10), F1 Kampung x broilers (35), and F2 Kampung x broilers (40). The PCR-RFLP and direct sequencing techniques were used to obtain mutations in the intron 4 of TGF-β3 gene using the BslI restriction enzyme. The TGF-β3|BslI locus was polymorphic in all populations and three genotypes were found: CC, AA, and CA. No association was found between the three genotypes with the carcass components in F2 Kampung x broiler cross.